Bar-driven evolution and quenching of spiral galaxies in cosmological simulations. Issue 3 (17th November 2016) - Spinoso, Daniele; Bonoli, Silvia; Dotti, Massimo; Mayer, Lucio; Madau, Piero; Bellovary, Jillian
Abstract : We analyse the outputs of the cosmological 'zoom-in' hydrodynamical simulation ErisBH to study a strong stellar bar which naturally emerges in the late evolution of the simulated Milky Way-type galaxy. We focus on the analysis of the formation and evolution of the bar and on its effects on the galactic structure, the gas distribution and the star formation. A large central region in the ErisBH disc becomes bar unstable after z ∼ 1.4, but a clear bar starts to grow significantly only after z ≃ 0.4, possibly triggered by the interaction with a massive satellite. At z ≃ 0.1, the bar stabilizes and reaches its maximum radial extent of l ≈ 2.2 kpc. As the bar grows, it becomes prone to buckling instability. The actual buckling event, observable at z ≃ 0.1, results in the formation of a boxy-peanut bulge clearly discernible at z = 0. During its early growth, the bar exerts a strong torque on the gas and drives gas inflows that enhance the nuclear star formation on sub-kpc scales. Later on, as the bar reaches its maximum length and strength, the gas within its extent is nearly all consumed into stars, leaving behind a gas-depleted region in the central ∼2 kpc. Observations would more likely identify a prominent, large-scale bar at the stage when the galactic central region has already been gas depleted, giving a hint at the fact that bar-driven quenching may play an important role in the evolution of disc-dominated galaxies.